Dos versiones de realismo en torno a Wittgenstein - Yuan, María Sol (ARFIL y UNL, 2019)
The present work revolves around two realistic readings of the "second Wittgenstein", one of non-metaphysical character emerged in Cora Diamond's The Realistic Spirit (1991) and another,"realistic metaphysics", in H. Mounce's"Wittgenstein and Classical Realism" (2005). From the confrontation of both positions, the thread of critical reading that will lead our work will be that we cannot sustain any realistic position "metaphysics" (to name it in a very general way) in relation to the thesis of the second Wittgenstein. The practical background on which the descriptions of this author are based shows that non-metaphysical, contingent basis on which we base our facts, concepts and objectivity. This brings us closer to a notion of realism in which concepts and reality already have meaning beforehand as the praxis in which they take root guarantees our dealings with what surrounds us. The foundation is not the reason, the conscience, the correspondence or adaptation to a "naked" reality; it is the praxis, the common place and the balance between human beings and the world.